2012
DOI: 10.1002/adfm.201201698
|View full text |Cite
|
Sign up to set email alerts
|

Smart Design of Stable Extracellular Matrix Mimetic Hydrogel: Synthesis, Characterization, and In Vitro and In Vivo Evaluation for Tissue Engineering

Abstract: The simplicity and versatility of hydrazone crosslinking has made it a strategy of choice for the conjugation of bioactive molecules. However, the labile nature of hydrazone linkages and reversibility of this coupling reaction restricts its full potential. Based on the fundamental understanding of hydrazone stability, this problem is circumvented by resonance‐stabilization of a developing N2 positive charge in a hydrazone bond. A novel chemistry is presented to develop a resilient hydrazone bond that is stable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
129
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 116 publications
(134 citation statements)
references
References 41 publications
5
129
0
Order By: Relevance
“…These results suggested that the degradation of the HA hydrogels was accelerated at acidic pH because of the pH-sensitive cleavage of hydrazone bonds. Similar phenomenon was observed in the hydrazide-aldehyde crosslinking system in the literature (Oommen et al, 2013). The degradation products of LEV-PEG-LEV are biocompatible PEG and LEV (Hami, Amini, Khansan, Rezayat, & Gilani, 2014).…”
Section: Degradation Behaviorsupporting
confidence: 84%
See 3 more Smart Citations
“…These results suggested that the degradation of the HA hydrogels was accelerated at acidic pH because of the pH-sensitive cleavage of hydrazone bonds. Similar phenomenon was observed in the hydrazide-aldehyde crosslinking system in the literature (Oommen et al, 2013). The degradation products of LEV-PEG-LEV are biocompatible PEG and LEV (Hami, Amini, Khansan, Rezayat, & Gilani, 2014).…”
Section: Degradation Behaviorsupporting
confidence: 84%
“…Moreover, the characteristic peak of hydrazone bonds at 1638 cm −1 could be noticed in the FT-IR spectra of the HA hydrogels by comparing these spectra and that of DTPH-HA, although their typical sharp absorption peak was not observed. The reason for this is that the peak was overlaid by the two strong characteristic peaks of amide groups at 1663 and 1618 cm −1 (Oommen et al, 2013). The spectrum line between the two absorption peaks became more smooth as the degree of crosslinking of HA hydrogels increased.…”
Section: Fabrication Of Ha Hydrogelsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is expected since it has been shown that changing the structure of the dihydrazide group used as a cross-linker can affect hydrazone bond stability by increasing resonance stabilization by shortening the carbon chain between hydrazide groups. 40 …”
Section: Resultsmentioning
confidence: 99%